2004
DOI: 10.1089/hum.2004.15.934
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Delivery of Glial Cell Line-Derived Neurotrophic Factor into Rat Striatum, Using a Tetracycline-Dependent Lentiviral Vector

Abstract: In this study, a tetracycline-regulated lentiviral vector system, based on the tetracycline-dependent transactivator rtTA2(S)-M2, was developed for controlled expression of glial cell line-derived neurotrophic factor (GDNF) in the rat brain. Expression of the marker gene green fluorescent protein (GFP) and GDNF was tightly regulated in a dose-dependent manner in neural cell lines in vitro. Injection of high-titer lentiviral vectors into the rat striatum resulted in a 7-fold induction of GDNF tissue levels (106… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 34 publications
(38 reference statements)
2
61
0
Order By: Relevance
“…This result is similar to other reports where inducible vectors have been used to control the release of GDNF following direct injection of viral vectors to the brain, but only met with limited Human neural progenitors releasing GDNF S Behrstock et al success. 43 There are a number of reasons why regulation cannot be achieved in vivo. Perhaps the most parsimonious of these is that GDNF may have a long-half life when compared to TH or destabilized GFP although there is limited evidence in the literature at present.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to other reports where inducible vectors have been used to control the release of GDNF following direct injection of viral vectors to the brain, but only met with limited Human neural progenitors releasing GDNF S Behrstock et al success. 43 There are a number of reasons why regulation cannot be achieved in vivo. Perhaps the most parsimonious of these is that GDNF may have a long-half life when compared to TH or destabilized GFP although there is limited evidence in the literature at present.…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviral vectors were produced as previously described 27 . These vectors were titrated using flow cytometry and quantitative PCR analysis as previously described 28 . The titres of the vectors in this study were in the range of: 5 Â 10 8 -1 Â 10 9 TU per ml.…”
Section: Methodsmentioning
confidence: 99%
“…With the exception of two reports, 46,48 all the tetracycline-inducible HIV-1 vectors listed in the literature were constructed using the tet-on system. 49,50 The authors showed that the tetracycline approach applied to HIV-1 gene transfer vectors allows inducible expression, that is dose-dependent and rapidly switched on and off.…”
Section: Lentiviral Vectors In Cancer Immunotherapymentioning
confidence: 99%